Machine Learning in Cloud: Sentiment Analyzing System - Dyussembayev, Roman; Shahpasand, Maryam; ., . (International Journal of Engineering and Technology, 2018)
As the number of computer users increases, numerous content has been generated by them. Machine learning as one of the main direction of natural language processing, allows computer systems to extract various information from the generated content. Processing results determine the sentiments of the text to extract the author's emotional evaluation that is expressed in the text. The aim of the project was to develop the Sentiment Analyzing system by using Machine Learning algorithms on cloud-based system. The paper describes the development process of Sentiment Analyzing System in English language. Two Machine Learning algorithms, SVM and Naïve Bayes classifier, have been inspected and Cloud computing used to develop and publish web application. The testing results demonstrate the accuracy of the work in proposed method.